Physiology and Immunity of Honey Bees (Apis Mellifera) as a Factor of Disease Resistance - Syromiatnykov, Yurii; Tursunova, Kamola; Ishniyazova, Shakhista; Jaloliddin, Abdullayev (American Journal of Botany and Bioengineering, 2025)
Honey bees (Apis mellifera) are essential pollinators in natural and agricultural ecosystems, yet colony losses associated with infectious and invasive diseases such as varroatosis and nosematosis remain a global challenge. This study investigated the physiological, biochemical, and behavioral indicators of colony health and their relationship to survival outcomes. Data were collected from 36 colonies in Latvia between 2023 and 2024, including healthy controls, varroa-infested colonies, and colonies affected by Nosema ceranae. Hemolymph protein concentration, catalase activity, fat body index, and hygienic behavior were measured, while overwintering survival served as the integrative outcome. Results demonstrated that diseased colonies exhibited substantial declines across all indicators. Compared to healthy controls, varroa-infested colonies showed a 22% reduction in protein levels, a 24% decrease in catalase activity, and a 28% loss of fat body reserves, while nosematosis caused protein reductions of 13%, catalase suppression of 35%, and fat body depletion of 21%. Hygienic behavior declined by 30–35% in both diseased groups, further compromising colony resilience. Overwintering survival decreased from 92% in healthy colonies to 71.5% under varroatosis and 64.8% under nosematosis. To integrate these findings, a Composite Disease-Resistance Colony Index (DRCI) was developed, combining physiological and behavioral parameters with penalties for parasite loads. Logistic regression modeling confirmed that deviations in protein and catalase levels significantly predicted winter losses, with synergistic negative effects observed under combined varroa and nosematosis infestations. These results underscore the value of physiological and biochemical monitoring for early detection of colony decline. The proposed indices and predictive models provide practical tools for sustainable apiculture by enabling timely intervention, optimized resource allocation, and selection of resilient colonies. Ultimately, this integrative approach contributes to reducing colony mortality and supporting pollinator stability in temperate climates.